Force-of-infection of Taenia solium porcine cysticercosis: a modelling analysis to assess global incidence and prevalence trends - Dixon, Matthew A.; Winskill, Peter; Harrison, Wendy E.; Whittaker, Charles; Schmidt, Veronika; Sarti, E.; Bawm, S.; Dione, Michel M.; Thomas, Lian F.; Walker, M.; Basáñez, M.-G. (Springer, 2020)
The World Health Organization (WHO) called, in 2012, for a validated strategy towards Taenia solium taeniasis/cysticercosis control and elimination. Estimating pig force-of-infection (FoI, the average rate at which susceptible pigs become infected) across geographical settings will help understand local epidemiology and inform effective intervention design. Porcine cysticercosis (PCC) age-prevalence data (from 15 studies in Latin America, Africa and Asia) were identified through systematic review. Catalytic models were fitted to the data using Bayesian methods, incorporating uncertainty in diagnostic performance, to estimate rates of antibody seroconversion, viable metacestode acquisition, and seroreversion/infection loss. There was evidence of antibody seroreversion across 5 studies, and of infection loss in 6 studies measured by antigen or necropsy, indicating transient serological responses and natural resolution of infection. Concerted efforts should be made to collect robust data using improved diagnostics to better understand geographical heterogeneities in T. solium transmission to support post-2020 WHO targets.